2021
DOI: 10.3389/fgwh.2021.647072
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Effects of COVID-19 Infection in Pregnant Women and Their Newborns: A Systematic Review and Meta-Analysis

Abstract: Amidst the COVID-19 pandemic, there is a need for further research on its manifestation in pregnant women, since they are particularly prone to respiratory pathogens, like severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), due to physiological changes during pregnancy. Its effects on infants born to mothers with COVID-19 are also not well-studied, and more evidence is needed on vertical transmission of the disease from mother to infant and on the transmission of IgG/IgM antibodies between mother and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 68 publications
2
12
1
Order By: Relevance
“…In the meta-analysis of babies born to COVID-19 PCR-positive mothers, neutrophil levels were found to be higher than the control group, as in our study 12 . It has been shown that high neutrophil count, increased CRP values, PLR and NLR ratios in adult patient groups are very informative in determining the severity of the disease and in the follow-up of treatment [13][14][15][16]18 .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In the meta-analysis of babies born to COVID-19 PCR-positive mothers, neutrophil levels were found to be higher than the control group, as in our study 12 . It has been shown that high neutrophil count, increased CRP values, PLR and NLR ratios in adult patient groups are very informative in determining the severity of the disease and in the follow-up of treatment [13][14][15][16]18 .…”
Section: Discussionsupporting
confidence: 76%
“…Although it is said that the severity of the disease may be higher in newborns compared to older children as a result of inadequate immune response, mortality and morbidity rates were found to be lower 11 . In the meta-analyses, the immunoglobulin G (IgG) levels in babies born to COVID-19 PCR positive mothers were found to be higher than the normal population, and it was hypothesized that COVID-19 antibodies transmitted from the mother via the placental route protect the baby from active disease 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The anatomical and physiological changes seen during pregnancy placed pregnant women in the "high-risk population" for SARS-CoV-2 [1]; however, for the younger patients in our study, the risk of severe complications decreased. We also considered the possible repercussions associated with the vertical transmission of the virus, but RT-PCR detection of the virus in newborns was absent [1,3,5,[22][23][24][25][26][27][28][29]. The manifestations of SARS-CoV-2 infection in the pregnant population were similar to those described in the literature for the general population and from other studies on pregnant women [8,24,30].…”
Section: Discussionmentioning
confidence: 82%
“…A hospital-based prospective casecontrol study was performed to assess the comparison of inflammation and coagulation biomarkers (such as NLR, PLR, and D-dimer) The New ArmeNiAN medicAl JourNAl, Vol. 16 (2022), No 2, p. 25 1. Our analysis shows no statistically significant differences in maternal age and gestational age characteristics between groups (p>0.05).…”
Section: Study Design and Settingmentioning
confidence: 99%
“…16 (2022), No 2, p. Wardhana M.P. et al, [25][26][27][28][29][30][31][32] among the third trimester of expectant with a confirmed diagnosis of COVID-19. This study was carried out from January until June 2021 at the labor room of Obstetrics and Gynaecology, Dr Soetomo General Academic Hospital Surabaya, Indonesia.…”
mentioning
confidence: 99%